Lithostratigraphy and lithogeochemistry of Ediacaran alkaline basaltic rocks of the Musgravetown Group, Bonavista Peninsula, northeastern Newfoundland, Canada: an extensional volcanogenic basin in the type-Avalon terrane - Mills, Andrea; Sandeman, Hamish (Atlantic Geoscience, 2021)
Volcanic rocks of the Ediacaran Musgravetown Group on Bonavista Peninsula, Avalon terrane, Newfoundland, include basal ca. 600 Ma calc-alkaline basalt succeeded by continental tholeiite and alkaline rhyolite of the ca. 592 Ma Plate Cove volcanic belt (Bull Arm Formation), indicating a change from subduction-related to extensionrelated tectonic regimes during that interval. Alkalic basalts on northeastern (Dam Pond area) and southwestern (British Harbour area) Bonavista Peninsula occur below and above, respectively, the ca. 580 Ma glacial Trinity facies. Dam Pond basalt occurs in a structural dome intercalated with and flanked by fine-grained, siliciclastic deposits (Big Head Formation) overlain by Trinity facies. The British Harbour basalt occurs above the Trinity facies, in an upward- coarsening sandstone sequence (Rocky Harbour Formation) overlain by red beds of the Crown Hill Formation (uppermost Musgravetown Group). The Rocky Harbour and Big Head formations are likely stratigraphically interfingered proximal and distal deposits, respectively, derived from erosion of the Bull Arm Formation and older Avalonian assemblages. The Big Head basalts have lower SiO2, Zr, FeOT, P2O5, TiO2 and higher Mg#, Cr, V, Co and Ni contents, and are therefore more primitive than the more FeOT-, TiO2-, and P2O5-rich British Harbour basalts. Large-ionlithophile and rare-earth-element concentrations and ratios indicate that both suites originated from low degree partial melts of deep, weakly garnet-bearing, undepleted asthenospheric peridotite sources, with magma conduits likely focused along regional extensional faults. The protracted and episodic extension-related volcanic activity is consistent with a geodynamic setting that evolved from a mature arc into extensional basins with slowly waning magmatism, possibly involving slab rollback and delamination followed by magmatic underplating. The duration and variation of both volcanism and sedimentation indicate that the Musgravetown Group should be elevated to a Supergroup in order to facilitate future correlation of its constituent parts with other Avalonian basins.